Efficacy of Anodonta anatina mussel in filtering Flavobacterium columnare - Hajisafarali, Mahsa (2018)
In this study the ability of the common freshwater mussel Anodonta anatina, to filter Flavobacterium columnare in comparison to their ability to capture algal cells (commercial phytoplankton product), was investigated. The mean concentration of F. columnare increased from 1.8 and 2.2 x 107 CFU mL-1 (0 h) to 9.1 x 107 and 1.45 x 108 CFU mL-1 after 48 h of experiment and then decreased to 4.9 and 9.3 x 107 by the end of experiment (96 h) in treatments with and without mussel, respectively. F. columnare was found in the intestine of mussels exposed to the bacteria suggesting the ability of A. anatina to filter bacteria from water and ingest them. There was a drastic decline in mean concentration of algal cells both with and without mussel by the end of the experiment, but the difference between the two treatment groups was not statistically significant, indicating that A. anatina did not filter commercial algae. This and the high amount of pseudofaeces in treatment where mussels received algal cells may imply that the commercial phytoplankton product was not appropriate food for A. anatina. Mussels reduced concentration of F. columnare by a factor of 1:2. Thus, the present results suggest that A. anatina may remove the fish pathogen F. columnare from water.